Methicillin-Resistant Staphylococcus aureus Outbreak in a Veterinary Teaching Hospital: Potential Human-to-Animal Transmission - Seguin, Jennifer C. (American Society for Microbiology, 1999)
During a 13-month period, 11 equine patients visiting a veterinary teaching hospital for various diagnostic and surgical procedures developed postprocedural infections from which methicillin (oxacillin)-resistant Staphylococcus aureus (MRSA) strains were isolated. The S. aureus isolates were identified by conventional methods that included Gram staining, tests for colonial morphology, tests for clumping factor, and tests for coagulase and urease activities and were also tested with the API STAPH IDENT system. Antimicrobial susceptibility tests were performed by the disk diffusion method. The biochemical profile and antibiogram of each isolate suggested that the isolates may have come from a common source. Because MRSA strains are very uncommon animal isolates but are rather common human isolates, a nasal swab specimen for culture was collected voluntarily from five persons associated with equine surgery and recovery in an attempt to identify a possible source of the organisms. MRSA strains were isolated from three of the five people, with one person found to be colonized with two biotypes of MRSA. The MRSA isolates from the people appeared to be identical to the isolates from horses. Further study of the isolates included SmaI and EagI macrorestriction analysis by pulsed-field gel electrophoresis conducted in two different laboratories. The results indicated that both the equine and human isolates were members of a very closely related group which appear to have originated from a common source. On the basis of the pattern associated with the infection, it is speculated that the members of the Veterinary Teaching Hospital staff were the primary source of the infection, although the specific mode of transmission is unclear.